2015
DOI: 10.4049/jimmunol.1403003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Toll/IL-1 Receptor Homologous Region Adaptors Act as Negative Regulators in Amphioxus TLR Signaling

Abstract: Studies have shown that the basal chordate amphioxus possesses an extraordinarily complex TLR system, including 39 TLRs and at least 40 Toll/IL-1R homologous region (TIR) adaptors. Besides homologs to MyD88 and TIR domain-containing adaptor molecule (TICAM), most amphioxus TIR adaptors exhibit domain architectures that are not observed in other species. To reveal how these novel TIR adaptors function in amphioxus Branchiostoma belcheri tsingtauense (bbt), four representatives, bbtTIRA, bbtTIRB, bbtTIRC, and bb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Amphioxus SARM plays an inhibitory role in both TICAM- and MyD88-dependent pathways, by interacting with TRAF6, MyD88, and TICAM ( 140 , 141 ). Furthermore, Peng and colleagues found that bbtTIRC inhibits bbtMyD88-mediated signaling by interacting with bbtMyD88 and suppressing bbtTRAF6 polyubiquitination, whereas bbtTIRA inhibits bbtTICAM-mediated activation of NF-κB through interacting with both bbtRIP1b and bbtTICAM ( 142 ). Since genes encoding bbtTIRA and bbtTIRC are NF-κB targets, these two proteins are likely to constitute an effective feedback regulation mechanism of amphioxus NF-κB signaling.…”
Section: Tlrs In Amphioxusmentioning
confidence: 99%
“…Amphioxus SARM plays an inhibitory role in both TICAM- and MyD88-dependent pathways, by interacting with TRAF6, MyD88, and TICAM ( 140 , 141 ). Furthermore, Peng and colleagues found that bbtTIRC inhibits bbtMyD88-mediated signaling by interacting with bbtMyD88 and suppressing bbtTRAF6 polyubiquitination, whereas bbtTIRA inhibits bbtTICAM-mediated activation of NF-κB through interacting with both bbtRIP1b and bbtTICAM ( 142 ). Since genes encoding bbtTIRA and bbtTIRC are NF-κB targets, these two proteins are likely to constitute an effective feedback regulation mechanism of amphioxus NF-κB signaling.…”
Section: Tlrs In Amphioxusmentioning
confidence: 99%
“…Membrane bound TLR4 recognizes LPS and signals with enhanced efficiency after forming a receptor complex with accessory proteins including myeloid differentiation protein 2 (MD-2), LPS binding protein, and CD14 [1113]. Docking the LPS-CD14 complex onto the TLR4/MD-2 complex initiates signaling through both the myeloid differentiation primary response 88 (MyD88) and Toll/IL-1 receptor-domain-containing adapter-inducing interferon-β (TRIF) pathways [14]. MyD88-dependent signaling activates nuclear factor-κB (NF-κB) and leads to the production of pro-inflammatory cytokines such as IL-6, tumor necrosis factor α (TNF-α) and IL-12.…”
Section: Introductionmentioning
confidence: 99%
“…Jalview was used for editing and viewing sequence alignments (62). The transmembrane regions of Aeg1 were predicted by the SMART Web site (63) .…”
Section: Methodsmentioning
confidence: 99%